A novel microparticle size sorting technology based on sheath flow stable expansion regimes - Zhang, Boran (2023)
Previously we have originally reported and experimentally explored the stable expansion phenomenon of sheath flow in straight microchannels. The stable expansion phenomenon differs from the focused stable thread and diffusion, which are expected to appear based on current understanding. It happens within a specific range of Reynolds numbers in microchannels with specific aspect ratios. However, the mechanism insight and potential applications remained poorly understood. In this study, a comprehensive numerical model, involving laminar flow, diluted species transportation, and particle tracing, was established to provide a global transparent insight. Based on the simulation results, the root cause and mechanism of the stable expansion phenomenon were revealed as a dumbbell-shape deformation of the buffer-sample-buffer interface. In addition, a microparticle size sorting application based on these findings was proposed and conducted in both simulation and experiment. The results showed that 1 and 15 μm microparticles can be totally separated with nearly 100% purity. According to the advantages and potentials of this technique, it can be promising to approach a label-free microparticle sorting with a high throughput manner.